Розвиток ринку земель сільськогосподарського призначення через механізм консолідації земель - Попов, Андрій Сергійович; Popov, Andriy (Київ : 2018, 2018)
UA: Мета статті - обгрунтувати усунення перешкод на шляху запровадження ринкового обігу земельних ділянок сільськлгосподарського призначення та його розвитку через їх консалідацію. Методика дослідження. Використано загальнонаукові і економічні методи: діалектичний, дедуктивний, аналізу та синтезу, системного аналізу. Результати дослідження. Висвітлено основні проблеми, які заважають відкриттю повноцінного ринку земель, а консалідацію земель сільськогосподарського призначення розглянуто як один із механізмів їх вирішення. Обгрунтовано модель запровадження регульованого ринку земель сільськогосподарського призначення через консалідацію земель. Введено поняття "активний обіг земельних ділянок" та надано характеристику процесу. EN: The purpose of the article is to justify the elimination of existing obstacles to the introduction of market turnover of agricultural land and the land market development through the land consolidation. Research methodology has been based on the elaboration of scientific publications of Ukrainian and foreign authors by using general scientific and special economic methods: the dialectical method, methods of analysis and synthesis, the method of system analysis and deductive method. Research results. The main problems that hinder the opening up of a complete land market have been highlighted and the agricultural land consolidation has been considered as one of the mechanisms for their solution. The model of the introduction of a regulated agricultural land market through land consolidation has been proposed. The concept of “land parcels mobility” and the characteristic of this process have been provided. Elements of scientific novelty. Scientific novelty of the article lies in implementation of land consolidation as a mechanism for solving problems that impede the introduction of agricultural land market. It has been empirically proven that land consolidation contributes to the prevention of possible risks during transactions to land parcel and land rights. The usefulness of introducing the concept of “land parcels mobility” in the framework of land consolidation has been actualized. Practical significance. Opening of a full-fledged agricultural land market in the framework of land consolidation will make enable to identify and fix the weaknesses of land legislation, discover trends in the formation of demand and supply, find out the factors of land mobility and land price formation. Figs.: 1. Refs.: 15.
Development of the agricultural land market through a mechanism of land consolidation
Keywords: консолідація земель; обіг земельних ділянок; ринок земель; землі сільськогосподарського призначення; право на землю; земельна ділянка; land consolidation; turnover of land parcels; land market; agricultural land; land rights; land parcel